EFFECT OF INFLATION, BI RATE AND EXCHANGE RATE ON SHARIA-LIFE INSURANCE PROFIT - Nasyifa, Intan Dwi; Nurdiansyah, Dian Hakip (Jurnal Ilmiah Wahana Pendidikan, 2023)
Indonesian people's awareness of the importance of insurance is increasing, including sharia insurance products. With increasing public awareness of Islamic insurance, it is possible that the income earned by Islamic insurance companies will increase. However, as people's awareness of insurance increases, economic conditions in Indonesia, such as the inflation rate, BI rate and exchange rates, also change. The economic conditions in Indonesia, which have often changed recently, were caused by the Covid-19 pandemic. Based on previous research and several theories, inflation, BI Rate, and also the Exchange Rate affect the profit earned by sharia-life insurance companies in Indonesia. Therefore, this study aims to find out whether economic conditions such as the level of inflation, the BI Rate, and the exchange rate also affect the profits earned by sharia life insurance companies in Indonesia. This research uses quantitative methods. This research includes these classic assumptions, that are Normality Test, Multicholinearity Test, Heteroschedasticity Test, and Autocorrelation Test. This research also conducts a hypothesis test consisting of t-test (partial test), Adjusted R Square test, and F test (Fisher Test). The results of this study the simultaneous influence of Inflation, BI Rate, and Exchange Rate on Sharia-Life Insurance Profit is 57.6%.